Geological and anthropogenic controls on the sampling of the terrestrial fossil record: A case study from the dinosauria - Upchurch, P; Mannion, P; Benson, R; Butler, R; Carrano, M (2011)
Dinosaurs provide excellent opportunities to examine the impact of sampling biases on the palaeodiversity of terrestrial organisms. The stratigraphical and geographical ranges of 847 dinosaurian species are analysed for palaeodiversity patterns and compared to several sampling metrics. The observed diversity of dinosaurs, Theropoda, Sauropodomorpha and Ornithischia, are positively correlated with sampling at global and regional scales. Sampling metrics for the same region correlate with each other, suggesting that different metrics often capture the same signal. Regional sampling metrics perform well as explanations for regional diversity patterns, but correlations with global diversity are weaker. Residual diversity estimates indicate that sauropodomorphs diversified during the Late Triassic, but major increases in the diversity of theropods and ornithischians did not occur until the Early Jurassic. Diversity increased during the Jurassic, but many groups underwent extinction during the Late Jurassic or at the Jurassic/Cretaceous boundary. Although a recovery occurred during the Cretaceous, only sauropodomorphs display a long-term upward trend. The Campanian-Maastrichtian diversity 'peak' is largely a sampling artefact. There is little evidence for a gradualistic decrease in diversity prior to the end-Cretaceous mass extinction (except for ornithischians), and when such decreases do occur they are small relative to those experienced earlier in dinosaur evolution. © The Geological Society of London 2011.